Vancomycin-Resistant Enterococci and Extended-Spectrum β-Lactamase-Producing Bacterial Colonization of the Cervix after Emergency Cerclage: Is It Safe? - Won-Kyu Jang; Jin-Gon Bae (MDPI AG, 2021)
Antimicrobial resistance is currently becoming a global threat to human health. We performed a retrospective study on patients who underwent emergency cerclage between January 2016 and December 2018 at the Dongsan Medical Center. Cervical culture was first performed before surgery to confirm that there was no infection and was repeated on days 1, 4, and 7 after surgery. A total of 85 pregnant women underwent emergency cerclage. Among them, six patients had vancomycin-resistant enterococci (VRE) colonization in the cervix after cerclage, and 23 patients developed extended-spectrum β-lactamase (ESBL)-producing bacterial colonization in the cervix. The average gestational age at delivery was lower in the VRE group. Neonatal death was also significantly higher in the VRE group. The rate of occurrence of early-onset sepsis was also higher in the VRE group, and both VRE and ESBL-producing bacterial colonization cases in which early-onset sepsis occurred resulted in neonatal death. The prognosis of cervical VRE colonization after cervical surgery was poor, whereas the prognosis of ESBL-producing bacterial colonization in the cervix did not differ significantly from that of the control group. However, careful neonatal treatment is required considering that early-onset sepsis is fatal to the newborn.